2005
DOI: 10.1074/jbc.m414014200
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Eukaryotic Translation Initiation Factor 4GI (eIF4GI) Proceeds from Multiple mRNAs Containing a Novel Cap-dependent Internal Ribosome Entry Site (IRES) That Is Active during Poliovirus Infection

Abstract: Eukaryotic translation initiation factor 4GI (eIF4GI)is an essential scaffolding protein required to recruit the 43 S complex to the 5-end of mRNA during translation initiation. We have previously demonstrated that eIF4GI protein expression is translationally regulated. This regulation is mediated by cis-acting RNA elements, including an upstream open reading frame and an IRES that directs synthesis of five eIF4GI protein isoforms via alternative AUG initiation codon selection. Here, we further characterize eI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…Curiously, however, the internal ribosome entry site-mediated translation of eIF4GI still demonstrates cap-dependence. 15 It has also been suggested that rapamycin causes decreased transcription of the eIF4G gene and, additionally, can enhance the rate of proteolysis of the initiation factor. 16,17 We cannot formally rule out the possibility that rapamycin regulates the expression of eIF4GI by such mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, however, the internal ribosome entry site-mediated translation of eIF4GI still demonstrates cap-dependence. 15 It has also been suggested that rapamycin causes decreased transcription of the eIF4G gene and, additionally, can enhance the rate of proteolysis of the initiation factor. 16,17 We cannot formally rule out the possibility that rapamycin regulates the expression of eIF4GI by such mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it has been shown that in a Krebs-2 in vitro system, or in an RNA transfection assay, an mRNA with the 900 nt (60% GC) LINE-1 5 0 -UTR, is translated by the cap-dependent scanning mechanism at 50% relative efficiency compared to the b-globin 5 0 -UTR (Dmitriev et al 2007). It should also be noted that some long 5 0 -UTRs with apparent IRES activity have subsequently been shown to be incompletely spliced variants with retained introns (Baranick et al 2008), for example the original eIF4GI 5 0 -UTR studied by Gan and Rhoads (1996), in contrast to the eIF4GI 5 0 -UTRs described by Johannes and Sarnow (1998) and Byrd et al (2005).…”
Section: Cellular Mrna Iressmentioning
confidence: 99%
“…The 3Ј ss in the putative eIF4G IRES is known to be used in formation of several of the eIF4G transcript variants (SI Fig. 12 A) (25). In transcript variant 5, which contains the proposed IRES and is transcribed from its own promoter, the 3Ј ss is not thought to be used.…”
Section: Six Putative Cellular Iress Exhibit Little Activity In a Dicmentioning
confidence: 99%